10 Years of Adult Learning (2006-2015): Content Analysis of a Journal - Catherine A Cherrstrom (Adult Education Research Conference, 2016)
Academic publications provide insight into a discipline’s history, knowledge base, and research norms, and analyzing a journal’s publication activity provides learning about the field of study. This study examines 10-year trends (2006-2015) in Adult Learning to learn and inform the field of adult and continuing education.
Keywords: adult and continuing education; Adult Learning; academic journal; content analysis